(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sofian A, Suhermanto A, Saidin, Sayuti M, Novianto D, Widyasari F. 2021. Short communication: Environment and morphometric of sea hare Dolabella auricularia from shrimp pond, Sorong West Papua, Indonesia. Biodiversitas 22: xxxx. Dolabella auricularia is a herbivorous marine biota living on the shallow seabed, which is found mostly in Indo-Pacific waters. The purpose of this study was to analyze the environmental and morphometric characteristics of Dolabella auricularia which live in vaname shrimp pond, Sorong, West Papua, Indonesia. Samples were collected from April to June 2020. From the measurement of pond waters environmental conditions, the following data were obtained: temperatures ranging from 31.47 ± 1.08oC, salinity ranging from 31.91 ± 2.29 ppt, pH ranging from 8.02 ± 0.20, brightness 108.00 ± 45.63 cm, and Dissolved Oxygen (DO) ranging from 4.10 ± 0.22 mg/L. The morphometrics of D. auricularia consisted of R-Anterior resp distances with sizes ranging from 38.9 ± 17 mm, wet weight ranging from 170 ± 34 g total lengths ranging from 112 ± 57.83 mm, posterior diameters ranging from 71 ± 41 mm. D. auricularia was found in pond waters as a pest for shrimp culture. However, D. auricularia also has biomedical and economic potentials as raw materials for the pharmaceutical industry. So, further studies are needed for their development.